'Forward from Wigan Pier': Remaking Documentary Photography in the 1930s. Issue 2 (4th May 2018) - Dell, Simon
Abstract : This article reconsiders the status of documentary photography by shifting enquiry from the making of the exposure to the processes that make the results of that act public. Instead of granting that a photograph functions in a semantic field and asking 'How did this signify?', this article explores the question: 'How did this have the opportunity to signify?' This question is addressed by exploring the agency of editors and publishers in the rather fraught production of George Orwell's The Road to Wigan Pier, the first edition of which featured a suite of thirty-three photographs.